Bangladesh divided : political and literary reflections on a corrupt police and prison state - Khan, Jalal Uddin (New York Peter Lang, 2019)
"This book examines the totalitarian police regime of Bangladesh, responsible, since 2009, for hundreds and thousands of killed and disappeared victims. This work is a contribution toward the need of the autocratic Awami's power to be openly examined. This book calls for peace, tolerance, compromise, social justice, rule of law, and democratically free and fair elections with level playing field for all concerned, especially the major political parties. This book will interest students and scholars of Bangladesh studies as well as South Asian (regional) specialism all around the world"--
Includes bibliographical references and index.
Keywords: Political corruption; Political violence; Authoritarianism